DETERMINERS OF THE MAIN LIVESTOCK COMMODITIES OGAN KOMERING ULU DISTRICT: DETERMINERS OF THE MAIN LIVESTOCK COMMODITIES OGAN KOMERING ULU DISTRICT - Yenni Sihite; Firda Novalia; Ahmad Iskandar; Putri Ayu Ogari (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2020)
This study aims to (1) determine agricultural subsectors seed, (2) identify the main commodity agriculture sector with the potential to be developed as a driver of the economy in K abupaten Ogan Ogan Ulu , (3) determine the structure and pattern of growth of the subsector and agricultural commodities featured in K Ogan Komering Ulu Regency . The method used is a purposive method . The data used are time series data that is secondary data of OKU Regency GRDP at current prices (2013-2017 ) and data on the area of production of agricultural commodities over a period of 5 years (2014-2018 ). The analysis shows that the estate crops sub-sector is the leading agricultural sub-sector in OKU Regency . Main commodities of livestock subsector are dairy cows, beef cattle , buffalo horses , sheep, and pigs . The patterns of growth in agriculture and leading commodities in the Ogan Komering Ulu Regency consist of: the plantation and forestry sub-sectors as fast-growing subsectors. While the food crops sub-sector is an advanced but depressed sub-sector, while Animal Husbandry and Fisheries are among the relatively sub-sectors. Leading commodities in the livestock farming sub-sector such as beef cattle are advanced and fast developing commodities; while goats and sheep are included in developing commodities ; while dairy cows are commodities that are relatively left behind.